PURWARUPA SISTEM PAKAR UNTUK PENYUSUNAN LAPORAN KEUANGAN (KASUS: UNIVERSITAS GADJAH MADA) - , RIYANTO ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Universitas Gadjah Mada as well as a legal entity BHMN (State Owned Legal Entity), and leads to the BHP (Legal Education) and is currently experiencing a transition to a form of BLU (Public Service Board) has a present obligation as a transparent financial reporting accountability to the public. The report presented both per unit of work or a combination of all work units in UGM and prosecuted on time every half year and full year to be audited by Certified Public Accountants. The condition of the tiered unit makes the process of preparing a complex report. To realize these targets will require an application that can prepare quickly and accurately reports beginning with the proper recording of all transaction journals. Inaccuracy of the transaction journal will provide incorrect information as well and affect the decision-making. In addition, the application also must be operated by operators who are not educational background in accounting, given that not all units have a qualified operator and often have difficulty. So that the necessary tools for operators to be able to do the job properly. One solution to this problem is to build a system that can guide the operator that no accounting background to use expert system. The results of this study is a prototype expert system for the preparation of financial statements of Universitas Gadjah Mada.